PERTUMBUHAN SENGON BUTOH PADA MEDIA TANAM BERBAHAN APU-APU (PISTIA STRATIOTES L.) DAN ECENG GONDOK (EICHHORNIA CRASSIPES) - Fadhil, Achmad Restu; Muryani, Eni; Prasetya, Johan Danu; Mussodaq, Mochamad (Universitas Pembangunan Nasional Veteran Yogayakarta, 2024)
Post-mining land restoration is a crucial effort in maintaining environmental quality. In post-mining land restoration, there are revegetation activities by replanting plants consisting of the nursery process to direct planting on the revegetation land. This study aims to observe the growth of sengon butoh plants for 30 days using planting media consisting of topsoil, apu-apu compost, and water hyacinth compost on the land of PT. Vale Indonesia Tbk. which is dominated by oxisol soil with low fertility. Apu-apu and water hyacinth are utilized through an anaerobic composting process for 30 days. Observations of sengon butoh growth are carried out every 10 days. Pearson correlation analysis and one-way anova tests are used to analyze the data, with measurements of growth parameters including the height and diameter of sengon butoh plant stems. The results showed that apu-apu compost and water hyacinth compost were proven to be able to support the growth of sengon butoh plants in a mixed planting medium of topsoil, apu-apu compost, and water hyacinth compost. Apu-apu compost showed a moderate correlation to the increase in plant diameter. One-way ANOVA test with post-hoc Games-Howell indicated a significant difference between treatments 7 and 6 in the increase in sengon butoh height.